Environmental contaminants: effects of microplastics on aquatic and terrestrial organisms (Research, Society and Development, 2021)
Intensified in the 18th century, environmental contamination has grown progressively around the world, radically generating toxic waste that proliferates every year. Among the most worrying pollutants of today, we highlight microplastics, small pieces of plastics less than 5 mm in diameter. The present work aims to carry out a literary survey focused on environmental impacts, showing the effects of microplastic on aquatic and terrestrial organisms. The search for the theoretical references used was carried out on websites of complete reliability, and scientific articles, dissertations and e-books were pre-selected for analysis. The criteria established for choosing the revised material came from reading the title and abstract. Given the analyzed literature, it was clearly noticeable that microplastics negatively affect directly and / or indirectly aquatic and terrestrial organisms, with ingestion being the main route of biotic contamination.